Psychological mechanism of the ancient-oriental Reiki technique: rehabilitation and (self)restoration of the psychosomatic state of human body. [Психологічний механізм давньосхідної техніки Рейкі: реабілітація та (само)відновлення психосоматичного стану організму людини] - Ivanchenko, Andreyanna; Iванченко, Андреянна Олексіївна (Харків : Видавництво НУЦЗУ, 2022)
Effective bioenergetic therapy Reiki leads to a significant reduction in unwanted affective-behavioral response, allowing a person to effectively overcome stress, rationally use own phenomenal natural arsenal and control its power. At the same time, Reiki not only improves the somatic-physiological functioning of the individual’s body and replenishes its protective and compensatory resources, but also normalizes the circulation of the psycho-bio-energetic flow (and therefore stabilizes the biofield). Thereby, it provides psycho-stability and emotional balance, and mainly, its cumulative positive effect is the normalization of physiological and somatic parameters during the functioning of the body. Nowadays, the use of Reiki technique seems to be especially relevant: on the one hand, there is an urgent need for training/rehabilitation of personnel of professional contingents of the security sector, defense and emergency rescue teams of Ukraine, both before and after their staying in extreme conditions; on the other hand, Reiki will significantly optimize the work with the general population (including with people who remained in the war zones, and with refugees from these areas).

Ефективна біоенергетична терапія Рейкі призводить до значного зниження небажаної афективно-поведінкової реакції, дозволяючи людині ефективно долати стрес, раціонально використовувати власний феноменальний природний арсенал і контролювати його силу. При цьому Рейки не тільки покращує соматично-фізіологічне функціонування організму людини, поповнює його захисні та компенсаторні ресурси, а й нормалізує циркуляцію психобіоенергетичного потоку (і відповідно стабілізує біополе). Тим самим він забезпечує психостабільність і емоційну рівновагу, а головним чином його сукупний позитивний ефект полягає в нормалізації фізіологічних і соматичних параметрів життєдіяльності організму. У наш час застосування техніки Рейкі видається особливо актуальним: з одного боку, існує нагальна потреба у навчанні/реабілітації особового складу професійних контингентів сектору безпеки, оборони та аварійно-рятувальних формувань України як до, так і після перебування в екстремальних умовах; з іншого боку, Reiki суттєво оптимізує роботу із широким населенням (у тому числі з людьми, які залишилися в зонах бойових дій, і з біженцями з цих територій).
Keywords: ancient eastern Reiki technique; stress-resistance; protective-compensatory resources; self-healing of the human body; rehabilitation of personnel of professional contingents; psycho-energetic flow; biofield; стародавня східна техніка Рейкі; стресостійкість; захисно-компенсаторні ресурси; самовідновлення організму людини; оздоровлення особового складу професійних контингентів; психоенергетичний потік; біополе